ANALISIS KANDUNGAN ZAT PEMUTIH “KLORIN” PADA IKAN ASIN DI PASAR TRADISIONAL (PABEAN) SURABAYA TAHUN 2015 - Novi Alita Anuradha; AT. Diana Nerawati; Erna Triastuti (Poltekkes Kemenkes Surabaya, 2015)
Salted fish which uses Non Food Additives are often found in the community. Chlorine bleachmaterial is feared to be added to the salted fish sold in traditional markets. Chlorine is an importantchemical in water purification, disinfectant, bleach, and mustard gas.This is a descriptive research with the objective of determining the chlorine contained in somekinds of salted fish sold in